Guidance note for practitioners leveraging climate-smart villages for peace: Insights from a bundle of interventions in Senegal - Ramos, Cristina; Sarzana, Carolina; Renkamp, Theresa M; Cisse, Sokhna Ramatoulaye (2025)
This guidance note introduces the concept of the Peace-Positive Climate-Smart Village (CSV+), a model that integrates conflict sensitivity and peace-positive social inclusion into climate adaptation programming. Drawing on evidence from a case study in Kaffrine, Senegal, we explore how CSVs can be designed and implemented to be both conflict-sensitive and peace-positive. We present a set of actionable guidelines to transition from the current CSV model to a CSV+ approach.